EFFICACY OF VANCOMYCIN VERSUS LINEZOLID AGAINST COAGULASE-NEGATIVE STAPHYLOCOCCI IN VARIOUS CLINICAL SPECIMENS - Ehsan, Muhammad Murad; Fatima, Ghulam; Ismail, M. Owais; Memon, Zahida (Journal of Ayub Medical College Abbottabad, 2014)
Background: Worldwide increase in antibiotic resistance has become one of the major problems. Optimal and rationale use of antibiotic is important to prevent resistance against most of the bacteria including Coagulase-negative Staphylococci (CoNS), which has now been recognized as an important pathogen for nosocomial infections. This study was carried out to determine efficacy of vancomycin and linezolid against CoNS in various clinical specimens. Methods: A total of 2989 specimens of blood, pus and wound swab were collected from wards, casualty, intensive care units (ICU) and out-patient department (O.P.D), out of these, Staphylococci were isolated in 1017 specimens, of which 381 were identified as CoNS. Culture, gram stain, catalase, coagulase test and antimicrobial susceptibility pattern were done on these specimens according to clinical manual of microbiology. A total of thirteen most commonly used antibiotics were used in this study. Susceptibility testing was done by Kirby Bauer disc diffusion technique. Results: Antimicrobial resistance of these isolates were Amoxicillin (74.8%), Amoxicillin+clavulanate (32.8%), Ciprofloxacin (35.2%), Ofloxacin (33.6%), Ceftriaxone (30.4%), Erythromycin (58.3%), Clindamycin (16.3%), Kanamycin (52.2%) Fusidic acid (41.7%), Doxycycline (24.7%), Vancomycin (2.6%) and Linezolid (0.8%) respectively. Isolates obtained from blood were 45.9%. Conclusion: Vancomycin showed resistance against CoNS which is a real threat for currently applied therapy against methicilin resistant CoNS. However, linezolid efficacy is higher than vancomycin against CoNS in our study, which suggests that this drug may be considered superior to vancomycin for the treatment of infections associated with CoNS. Keywords: Coagulase negative Staphylococci, Antibiotic resistance, Vancomycin, Linezolid